Implementasi Model Pembelajaran “Introflex Terpadu” pada Mata Pelajaran Pendidikan Agama Islam dan Budi Pekerti di SMP Islam Terpadu Harapan Bunda Purwokerto - Aisia Sofiana, Hana; Harisatunisa (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
This study aims to describe the implementation of the Introflex TERPADU learning model in Islamic Religious Education and Character Education at SMP Islam Terpadu Harapan Bunda Purwokerto, as well as analyze student learning motivation. Teaching Islamic Religious Education and Character Education requires interesting teaching methods so that the material can be delivered well and display student learning motivation. This study uses a qualitative approach with a descriptive qualitative method and field research. Data were collected through interviews, observations, and documentation. Data analysis uses the Miles and Huberman model, which includes data reduction, presentation, and verification. The subjects of the study were teachers, students, principals, and deputy heads of curriculum of Islamic Religious Education and Character Education. The results indicate that the Introflex TERPADU learning model was implemented in three stages in the Islamic Religious Education and Character Education subjects at SMP Islam Terpadu Harapan Bunda Purwokerto: planning, implementation, and evaluation. This model visualizes learning. Implementing the Introflex TERPADU learning model requires good coordination from various parties due to the presence of supporting and inhibiting factors